O pewnym zastosowaniu algorytmów genetycznych do prognozowania szeregów czasowych - Kucharski, Adam (On the Use of Genetic Algorithms to Time Series Forecasting, 2007)
This paper presents how genetic algorithms can make forecasts of pretty complicated time series using simple naive methods. Moreover, it is possible to achieve adjustement of some kind for different types of time series. All this can be done thanks to flexibility of genetic algorithms. There had been carried out modifications in classic genetic algorithm. Some operators, like crossing or mutation, had been changed in order to adapt them to a certain parameter called tm. tm expresses maximum allowable lag of observation making current ex post forecast. This parameter, included in algorithm, had become the basis of presented prediction method.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 143-153